A study on industrial green transformation in China - Li Ping; Yang Danhui; Li Pengfei; Ye Zhenyu; Deng Zhou (Fondazione Eni Enrico Mattei (FEEM), 2013)
China's speedy industrialization has undertaken mostly a crude path with extensive energy consumption and severe environmental damage. In face of the challenge of global warming and resource restrictions, it calls for urgent green transformation for the sustainable development of China's industry. With huge potentials and more general benefits than costs, the industrial green transformation in China will have more positive effects and accelerate the whole process of the development of China's green economy. From this perspective, China needs to adopt a comprehensive and open mechanism for green transformation with more strict environmental regulations, effective energy conservation and emissions reduction, green technology R&D and application, as well as international cooperation in the related fields with market-oriented reform, government strategies and regulations, proactive response from the industry sector, self-initiative of enterprises and active public participation.
Keywords: Q5; Q55; 330; Industry; Green Transformation; Technology Roadmap; Cost and Benefit